Thermodynamic Parameters and Viscosity Behaviour of Nitro Pyrazoline in 70% Methanol-Water - Deshmukh, C.C.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
Viscosity measurements have been made on system 3-(2"-hydtoxy- 3"-Nitro-5" -cblorophenyl)-5-(2' -furyl) pyrazoline in 70% methanol-water solvent at different temperatures. The data have been used to calculate viscosity and thermodynamic parameters such as ΔG*, ΔH* and ΔS* . We have also studied the effect of solvent on viscosity at 25°C. It has been found that viscosity increases with increase in the percentage of solvent methanol. We have also calculated the thermodynamic parameters ΔG*, ΔH* and ΔS* for nitropyrazoline, which shows that the process is spontaneous and irreversable.